Implementasi Model Kooperatif Tipe Jigsaw dalam Pembelajaran PAI dan Budi Pekerti - Windiarti, Windiarti; Yahya, M. Slamet (Jurnal Pendidikan Agama Islam, 2025)
This research is motivated by the need for the application of learning methods to increase students' interest, understanding, and active involvement in Islamic Religious Education (PAI) learning, because the problem often faced is the lack of student interest in PAI learning when using conventional methods, so innovative learning is needed from teachers in the form of using learning models and methods. This study aims to describe the implementation of the jigsaw type cooperative model in Islamic Religious Education and Character Education learning at SMK Ma'arif NU 1 Ajibarang. This study uses a qualitative approach, with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the implementation of the jigsaw type cooperative model in Islamic Religious Education and Character Education learning is carried out through 3 stages, namely planning, implementation, and evaluation. The results of this study also show that the use of the jigsaw type cooperative model runs effectively and gets a positive response from students, in addition this method also increases cooperation between members, trains each individual's sense of responsibility, and encourages student involvement in learning so that the classroom atmosphere becomes more lively